SISTEM INFORMASI MONITORING DAN EVALUASI PERKULIAHAN (STUDI KASUS: STIKOM DINAMIKA BANGSA) - Fachruddin Fachruddin (LPPM Universitas Dinamika Bangsa, 2014)
Monitoring is a monitoring activity conducted to determine the activity of learning processes undertaken by the lecturer. While the evaluation itself is the end results of the monitoring result carried out during the teaching-learning process in one semester. Monitoring activity and the learning process evaluation are the activities carried out by the Chairman of the program in each study programs that aims to monitor the implementation of learning process standardization undertaken by the lecturers continuously and to take action based on the existing conditions. This study aims to establish a monitoring information system and learning evaluation at STIKOM Dinamika Bangsa Jambi based on the quality assurance system needs. Thus, learning prosess can be carefully monitored. Keywords: Information System, Monitoring, Evaluation, UML